Aminobisphosphonate‐treated ewes as a model of osteonecrosis of the jaw and of dental implant failure. Issue 5 (15th December 2019) - Davison, Mario R.; Lyardet, Leonardo; Preliasco, Mariana; Yaful, Graciela; Torres, Perla; Bonanno, Marina S.; Pellegrini, Gretel G.; Zeni, Susana N.
Abstract: Background: Bisphosphonate (BP)‐related osteonecrosis of the jaw (BRONJ) and dental implant failure are two negative side effects of chronic aminoBP treatment. Methods: Eleven ovariectomized (OVX) ewes and four ewes subjected to sham surgery (SHAM) were treated as follows: OVX ( n  = 5): OVX plus saline solution; zoledronic acid‐treated group (ZOL) ( n  = 6): OVX plus ZOL; SHAM ( n  = 4): SHAM plus saline solution. Extraction of the first upper molar was performed at 1 year, dental implant placement at 2 years, and sacrifice at 28 months. Results: Implants remained in place in SHAM and OVX ewes but were lost in all ZOL ewes. ZOL sheep (2/6) showed inflammation and necrotic bone at mandibular region. No differences in serum calcium (Ca), inorganic phosphate (Pi) or 25‐hydroxyvitamin D were observed, whereas bone alkaline phosphatase levels decreased in the three studied groups ( P  < 0.05). The significantly lowest levels of carboxy‐terminal telopeptide of type I collagen were observed in ZOL ( P  < 0.05), and showed no differences between SHAM and OVX. OVX showed the lowest and ZOL the highest Ca and Pi contents in femur and maxilla ( P  < 0.05). Bone volume (BV/TV%) and iliac crest were similar at baseline and at month 4. At the end of the study, BV/TV%, proximal femur and hemi‐mandible bone mineral content and bone mineral density, and trabeculae number were similar in SHAM and ZOL, and lower in OVX ( P  < 0.05). Conclusion: All ZOL‐treated ewes on a schedule similar to that used in cancer patients showed extensive suppression of bone remodeling and implant failure. Some of the ZOL ewes developed BRONJ.